WORK HARASSMENT, WORKING CONDITIONS AND HEALTH PROBLEMS PREVAILING IN GARMENT FACTORIES AND POWERLOOMS IN GADAG - A STUDY - Dr. Shobha N Dr. Rajappa L, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Indian Textiles and Apparels (T&A) and Power looms account for approximately 4% of global market. They are the largest and most significant sectors for Indian economy in terms of output, foreign exchange earnings and employment. The industry contributed 7% to the industrial output in value terms, 2% to the GDP and 15% to the country’s export earnings. T&A and Power looms are proving direct employment to the 45 million people and it is the second largest job provider after agriculture. As per WTO (World Trade Statistics Review 2018) India ranked 5th largest exporter of RMG in the world. There are 156 garment units and 841 sheds constructed in which more than 5,000 units are operating in 11 Power Loom areas spread in Gadag districts of Karnataka. around hosts several large scale garment companies, such as . Mcjbazaar.com. Rahul Collection M S Garments Rakesh Garment. M S Sportswear. Yuva Sports Garment, Osia Traders. Brand Shoppe & Co. and Power looms like Gadag Weavers Producr Company Limited, Seetamma Textiles , Padmavati Malleshappa Rangam, Ramesh Handloom & Powerloom Works, Basappa Powerlooms The apparel industry demand exports grew at a slightly slow CAGR of 13% firm 2432 billion in FY 2010 to Rs. 6484 billion in 2018 (Care ratings, 2019).